المواطنة عند فلاسفة العقد الاجتماعي - بلخيري, سارة (جامعة الوادي - University of Eloued, 2022)
تتناول هذه الورقة العلمية قضية تفسير المواطنة التي لها تأثير كبير على الفكر السياسي سواء كان قديما أو حديثا مع فلاسفة العقد الاجتماعي أمثال، "توماس هوبز"، "جون لوك" و"جون جاك روسو"، فهي من أبرز الأسس التي يمكن الاستناد عليها في تلاحم المجتمعات بين بعضها البعض أو بينها وبين الممثلين للسلطة فيها، وعلى هذا الأساس سنحاول في هذه الدراسة تحديد معنى المواطنة والاطلاع على حقيقتها خاصة عند أصحاب نظرية العقد الاجتماعي، مبينين أهم المسائل الخلافية في نظرة كل منهما لها، ونحن هنا نهدف إلى توضيح أصولها وأبعادها في فلسفتهم، بالاستعانة بالمنهج التحليلي المقارن، إذ ألزمنا أنفسنا على تحليل أفكار فلاسفة العقد الاجتماعي في قضية المواطنة، كاشفين عن أهم مواطن التباين بين وجهات نظرهم وعاملين على التقريب بينها، وبذلك يعتقد كل من "هوبز" و"جون لوك" أنها تقوم بإعطاء الحقوق للأفراد وتضمن استقرارهم في المجتمع من خلال تنازلهم على حقوقهم، لكن الاختلاف يكمن في أن الأول ـ "هوبز" ـ يقول بالتنازل على كل الحقوق، أمّا الثاني ـ "لوك" ـ يثبت أنّه لا يمكن للأفراد التنازل عن جميع حقوقهم، بينما يؤكد "روسو" أنها صفة تطلق على المساهمين في السلطة العليا القادرة على سن القوانين وتنفيذها. This scientific paper deals with the issue of the interpretation of citizenship, which has a significant impact on political thought, whether ancient or modern with philosophers of the social contract such as Thomas Hobbes, john Locke, and jean-Jacques Rousseau, the cohesion of societies between each other or between them and the representatives of the authority in them, and on this basis we will try in this study to define the meaning of citizenship and find out its reality, especially among the owners of the social contract theory, showing the most important controversial issues in their view of it, and here we aim to clarify its origins and dimensions in their philosophy, using the comparative analytical method, as we committed ourselves to analyzing the ideas of the philosophers of the social contract in the issue of citizenship, revealing the most important points of contrast between their views and working to bring them closer, and thus both Hobbes and john Locke says that it gives rights to individuals and guarantees their stability in society by compromising their rights, but the difference lies in the fact that the first – Hobbes – says to waive of all rights, while the second -Locke – proves that individuals cannot give up all their rights, while Rousseau asserts that it is an adjective given to the shareholders of the supreme power capable of enacting and implementing laws.
توماس هوبز، جون لوك، جون جاك روسو
مقال
Keywords: المواطنة؛ المواطن؛ الحق؛ نظرية العقد الاجتماعي; citizenship; citizen; right; social contract theory